Effect of hyperoxia and hypoxia on retinal vascular parameters assessed with optical coherence tomography angiography - Hommer, Nikolaus (2022)
To investigate the response of the superficial and deep capillary plexuses to hyperoxia and hypoxia using optical coherence tomography angiography (OCT-A) and retinal vessel analyzer.